The Meanings of the Cultural Landscape in Pantai Lido Waterfront According to Malay Oldies Perspective - Mohd Amirul Hussain , Nur Afikah Idrus , Mohd Yazid Mohd Yunos, Nor Atiah Ismail , Nor Fazamimah Mohd Ariffin , Sumarni Ismail (International Journal of Advanced Science and Technology, 2020)
Many researchers consider the definition of ‘Meaning’ as it plays an essential role, especially in the perspective of place image. The meaning of place is manifested through the symbolism of place that considered as universal as they represent the crucial tendencies of the human mind. The meaning of the place remains the precious memories that make such a memorable place as it can enhance the identity of the place. The objective of this study is to obtain the criteria of the cultural landscape elements that exist in Pantai Lido, which creates the meaning of the place in Pantai Lido waterfront according to the Malay oldies’ perspective. Furthermore, in achieving the objective, a qualitative method was conducted which involved in-depth interviews and participant observation by collecting the informants’ perception, memories, attitudes and beliefs as the subjective reality manifested at both of the psychological and social-cultural levels. The findings demonstrate the meaning of place as the factors that make Pantai Lido more noticeable and memorable. Moreover, the elements that make the cultural landscape in Pantai Lido more prominent is due to the local people’s place attachment and the environment that evoked its memories and meanings. This study will carry on by suggesting a survey on the importance of meanings of place and its association involvement in cultural landscape conservation. This indicates that perhaps the local authorities and the policymakers need to improve and reshuffle the current regulations for urban waterfront development in Malaysia